KAJIAN PENGENDALIAN RESIKO KESELAMATAN DAN KESEHATAN KERJA DENGAN METODE HAZARD INDENTIFICATION RISK ASSESSMENT AND RISK CONTROL ( HIRARC ) DI PT. LANGKAT NUSANTARA KEPONG - Mukti, Ismail; Ningsih, Tuty; Sibuea, Ishman L. (Jurnal Agro Fabrica, 2023)
PT. Langkat Nusantara Kepong is one of the KSO companies engaged in the oil palm plantation business. In carrying out the operational activities of one PKS unit, PT. Langkat Nusantara Kepong is supported by more than 100 workers who interact directly with machines and other work equipment. Every workplace contains a high potential for hazards, so a prevention and control effort is needed to prevent work accidents. The occurrence of work accidents is caused by the actions of people who do not comply with work safety (unsafe actions) and environmental conditions or processes from unsafe systems (unsafe conditions). Hazard Identification Risk Assessment and Risk Control (HIRARC) is an effort to prevent work accidents and OHS risks. This research was conducted using a qualitative descriptive method which describes the identification and assessment of work risks. Data collection regarding identification and risk assessment was analyzed with HIRARC. HIRARC Results at PKS Gohor Lama PT. Langkat Nusantara Kepong that the highest number of risk levels is at the boiler station.